Correction to: Chitooligosaccharides from squid pen prepared using different enzymes: characteristics and the effect on quality of surimi gel during refrigerated storage - Avtar Singh; Soottawat Benjakul; Thummanoon Prodpran (Food Production, Processing and Nutrition, 2019)
In the original publication of this article [1], the author point out the ‘3.18–4.77 CFU/g’ in sentence ‘At day 10, all counts were in the range of 5.49–6.57 and 3.18–4.77 CFU/g sample for gels added without and with COS-L’ should be ‘3.18–4.77 log CFU/g’.